Pengaruh Kinerja Dokter Gigi Terhadap Mutu Pelayanan dan Implikasinya Pada Kepuasan Pasien - Nurul Hidayah; Muhardi Muhardi; Sri Suwarsih (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Clinics and hospitals as public health care service s have to be able to maximize the available resources, namely dentists. The high number of oral health problems in Indonesia requires better dentist performance. This study aims to determine the performance of dentists, the quality of dental treatment services, patient satisfaction, and the effect of dentist performance on service quality and its implications for BPJS patient satisfaction at the primary clinic in Bandung. The study used pathway analysis methods to test the effect of intervening variables on dependent and independent variables This study involved 100 BPJS patients at the primary dental clinic from 28 sub-districts in Bandung City as samples. The results of the study showed that respondent’s perception of dentist performance variables indicated that dentists had a fairly good performance in providing health care services to BPJS patients at primary clinics. Respondent’s perception of service quality variables shows that dentists provide a fairly good service quality to BPJS patients at primary clinics. Respondent’s perception of the satisfaction variable showed that BPJS patients aere satisfied with health care services at primary clinic. It can be concluded that the dentist performance variable through service quality has a significant influence on patient satisfaction.